Peak business performance under pressure a Navy ace shows how to make great decisions in the heat of business battles - Driscoll, Bill; Nye, Peter 1947- (Allworth Press, 2014)
"In enemy airspace, high above the treetops of North Vietnam, two US F-4 Phantom jet fighters have downed their fifth enemy plane, thus securing their new status as "Aces." The skies are finally quiet, and the safety of the ocean is just ahead. But in that brief moment of victory, they are blindsided by a surface-to-air missile. Bill "Willy" Driscoll, one of the most highly decorated Naval Flight Officers of the alast fifty years, demonstrates how his TOPGUN training prepared him for both life-or-death aerial dogfights and the demands of difficult business decisions. His remarkable military experiences, his 26-year award-winning career in the highly competitive Southern California commercial real estate market, and personal interviews with twenty-six other Ace pilots and over 200 business executives serve as a blueprint for achieving extraordinary results under the most difficult circumstances organizations face each day. Topics include preparation, risk assessment, team building, focus and listening, self-evaluation and improvement, avoiding pitfalls, and much more."